2020
DOI: 10.7322/jhgd.v30.10360
|View full text |Cite
|
Sign up to set email alerts
|

Social distancing measures may have reduced the estimated deaths related to Covid-19 in Brazil

Abstract: Social distancing was planned as a preventive measure to control the extensive spread of COVID-19. COVID-19-related deaths in Brazil were analyzed during the period of social distancing measures. Mortality data for COVID-19 was obtained from the Worldometer website. Deaths were estimated up to the 31st day after the occurrence of the 5th COVID-19-related death in Brazil. Social distance was measured using Google's community mobility reports. The Brazilian epidemic curves were interconnected, and mathematical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 4 publications
0
22
0
Order By: Relevance
“…For example, 'social distancing' has been widely promoted as a Epidemiology and Infection measure to reduce the transmission of COVID-19 [53]. Valenti et al [54] used CMR data as an estimate of social distancing in the modelling of deaths in Brazil. However, CMR data indicate only general activity at specific location types, and provide no direct indication of adherence to such rules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, 'social distancing' has been widely promoted as a Epidemiology and Infection measure to reduce the transmission of COVID-19 [53]. Valenti et al [54] used CMR data as an estimate of social distancing in the modelling of deaths in Brazil. However, CMR data indicate only general activity at specific location types, and provide no direct indication of adherence to such rules.…”
Section: Discussionmentioning
confidence: 99%
“…Valenti et al . [54] used CMR data as an estimate of social distancing in the modelling of deaths in Brazil. However, CMR data indicate only general activity at specific location types, and provide no direct indication of adherence to such rules.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of non-pharmacological measures is urgent. Valenti et al, 5 demonstrated that social distance is an effective measure to control the extensive dissemination of COVID-19.…”
Section: Coronavirusmentioning
confidence: 99%
“…Nowadays, the dynamics of COVID-19 models have been growing interest in the research community and may mathematical models are designed for the better interest of people around the world, such as the model of eight classes based on susceptible, infected, diagnosed, ailing, recognized, threatened, healed and extinct (SIDARTHE) [6], five classes based on SEIAR represented with 5 number of ordinary differential equations [7], a new θ -SEIHRD model represented with nine classes [8], modified SEIRS model system with five classes [9], four class modified SIR model [10], SAIR system based COVID-19 model for complex networks [11]. Beside, these variety of COVID-19 model are introduced by the researchers [8,[12][13][14][15][16][17][18][19][20][21][22]. However, in the current scenarios, we have taken a complex 8 classes model based on Susceptible (S), exposed (E), symptomatic and infectious (I), super propagation (P), infection but asymptomatic (A), hospitalized (H), recovery (R) and fatality (F) classes, i.e., SEIPAHRF for numerical investigations [23].…”
Section: Related Studiesmentioning
confidence: 99%